Analysis of Financial Performance on Banking Companies That Are members of the Kompas100 - Sitio, Nurul M; Fatimah, Siti (CV ODIS, 2024)
Banking plays an important role in managing the wheels of economic transactions in a country's society. Therefore, as a financial institution that has an intermediary function, banks must demonstrate good financial performance through their financial ratios. The purpose of this study was to determine the effect of the ratio of Non Performing Loans, Loan to Deposit Ratios, and Operational Efficiency Ratio on Return on Assets in Kompas100 indexed banking in 2018-2020. There are eight research samples that meet the criteria in the purposive sampling method with data analysis using multiple linear regression. The findings of this study are Non Performing Loans and Loan to Deposit Ratio have a positive but not significant effect on Return on Assets, while Operational Efficiency Ratio have a negative and significant effect on Return on Assets. Simultaneously, NonPerforming Loans, Loan to Deposit Ratios, and Operational Efficiency Ratio have a significant effect on Return on Assets.